Error Made in Conversation by Indonesian Learners Learning English Based on Syntax and Exchanging Information - Wiannastiti, Melania (Humaniora, 2014)
In learning a second language or foreign language (L2), learners should master the competences. Normally, L2 learners first should master the linguistic competence which includes the mastery of vocabularies, pronunciation, and grammar. The study is to find out the syntax error made by L2 learners in conversation as well as to find out the exchanging information. The data were the recording conversation of Visual Communication Design students first semester of Binus University joining English Entrant. Error analysis was used to analyze the data. There are two points of view to analyze the data: syntax from taxonomy and exchanging information. Taxonomy employs the error in omission, addition, misinformation, and mis-ordering. Exchanging information point of view employs the error in finite element and mood. The result shows that L2 learners made some errors in grammar and exchanging information because they are influenced by the L1. They tend to transfer from L1 to L2 rather than thinking to create the utterances in L2.